Polycystic Ovary Syndrome is Associated with Elevated Periostin Levels - Chen, Xinwei; Huo, Lijing; Ren, Luping; Li, Yali; Sun, Yanmei; Li, Yang; Zhang, Pu; Chen, Shuchun; Song, Guang-yao (Experimental and Clinical Endocrinology & Diabetes, 2019)
Purpose Periostin is a secreted extracellular matrix protein that is strongly associated with triglyceride metabolism, chronic inflammation, and insulin resistance. Growing evidence suggests that there is a link between periostin and ovarian function. Our aim was to ascertain whether circulating periostin levels are altered in women with polycystic ovary syndrome (PCOS) and to further explore the relationship between periostin and glucose metabolism disorder in PCOS patients.Methods In total, 50 women with PCOS and 30 age-matched controls without PCOS were recruited for this cross-sectional study. Periostin levels were measured using ELISA as well.Results Circulating periostin levels were significantly elevated in PCOS women compared with controls [4206.75(222.00, 4815.25) vs. 430.75(142. 13, 730.86) ng/ml, P=0. 005]. Spearman’s correlation analysis showed that serum periostin levels had a positive correlation with body mass index (BMI), uric acid, homeostasis model assessment of insulin resistance (HOMA-IR), high-sensitive C reactive protein (hs-CRP), and a negative correlation with insulin sensitivity index (ISI). Logistic regression models revealed that PCOS was correlated with waist to hip ratio (WHR), fasting blood glucose (FBG), and periostin levels. In addition, multivariate linear regression analyses showed that FBG, HOMA-IR, and the lipid accumulation index (LAP) were independent factors influencing serum periostin levels.Conclusion PCOS is associated with elevated levels of periostin.
Keywords: polycystic ovary syndrome; periostin; insulin resistance; lipids; testosterone; sex hormone binding globulin; high sensitive c-reactive protein